"Supply Chain—Marketing Shark Tank" Experiential Lab Game in Interdisciplinary Business Education: Qualitative and Quantitative Analyses. (January 2015) - Arora, A.; Saxena Arora, A.
ABSTRACT This article provides educators in business schools with a new interdisciplinary experiential lab game called Supply Chain—Marketing (SC‐Mark) Shark Tank game, which can be implemented in both Supply Chain Management (SCM) and Marketing courses. The SC‐Mark experiential lab game is a real‐life business environment simulation that explores complexities in advertising industry service supply chains. One hundred sixty‐one undergraduate students participated in the game at two business schools over two semesters. The effectiveness of the game was measured and analyzed, qualitatively and quantitatively, based on text analysis of the feedback received from participating students. The results revealed five themes that helped student teams understand how advertising companies integrate and improve their service supply chains—buyer‐supplier relationships, supply chain functions and operations, consumer focus and orientation, community focus, and overall risk management.